Development of a Hi-Per strut front suspension - Johansson, Anders; Roubert, Peter (My University, 2011)
The aim of this master thesis has been to develop a front suspension of Hi-Per design suitable for a mid- or full size standard car. A Hi-Per suspension is a variant of the MacPherson strut suspension, with the difference of a steered knuckle and a rigid damper strut. In a MacPherson suspension the whole damper and knuckle assembly is steered, limiting the position of the steering axis by the body mounts of the strut. The designed suspension should fit into the same interface as a suspension of MacPherson type and should be applicable for three different models with different ride heights. The vehicles featuring the new Hi-Per suspension shall have an increased track width making an unchanged MacPherson suspension unsuitable with respect to kingpin offset based phenomena such as torque steer or influence of road disturbances. The base for the Hi-Per design was an available MacPherson vehicle and previous Saab vehicle models, of which one features a Hi-Per suspension design. Within the thesis, solutions available on the market today has been investigated and benchmarked as well as previous solutions within Saab. This has together with the free thinking of the designers hopefully form the best solution possible for the new Hi-Per design. The focus of the suspension has been to achieve a high level of commonality, at the same time as design requirements of packaging and kinematics are fulfilled together with maintenance and assembly improvements. Within the thesis a large effort has been used for packaging in CAD, at the same time as the geometry is verified by kinematic multi body simulations. This was done in order to fulfil wheel parameters and static design factors of the suspension. Within this thesis a complete pre-study has been performed. This pre-study has resulted in a design proposal, based on the simulation results incorporating Saab vehicle- and suspension requirements. The CAD-models have been designed with regards to clearance during bump, rebound and steering. The models have been designed with similar wall thickness and geometries as the existing Saab Hi-Per solution. The recommendations of this thesis are to continue working with the design proposal with regards to compliance calculations and more specific CAD-designs. There has not been any FE-analysis performed on the parts. Therefore there is a need to further investigate the CAD-models with regards to compliance calculations. Key words: Vehicle suspensions, Hi-Per, MacPherson, Torque steer, Product development, Mechanical engineering, Automotive
Keywords: Transport; Innovation och entreprenörskap (nyttiggörande); Teknisk mekanik; Transport; Innovation & Entrepreneurship; Applied Mechanics